Pendekatan Metode S-SDLC Untuk Perancangan Aplikasi Kasir Pada Toko Aldy Jaya Berbasis Website - Irfansyah, Aldy; Rahmi, Elvi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Aldy Jaya Store is a business that sells various necessities such as food, fishing equipment, fish supplies, and bird supplies. Currently, the store does not have a transaction recording system or stock management, which results in difficulties in obtaining sales reports and often disappoints customers due to the lack of real-time stock information. Therefore, this research aims to design a web-based cash register application that can effectively record sales transactions and monitor stock items, to facilitate reporting and store management. The development of this application uses the Secure Software Development Life Cycle (S-SDLC) approach, which includes identifying security needs, designing a secure system, developing protected code, testing security, implementing applications, and maintaining security. The results from the development show that this cashier application is capable of improving operational efficiency and maintaining data security. Through the implementation of data classification and role-based access control, this application not only serves as a recording tool but is also able to protect data from threats, maintain information integrity, and ensure optimal system availability.